Microbial regulation of nitrogen dynamics along the hillslope of a natural forest - Isobe, Kazuo; Ohte, Nobuhito; Oda, Tomoki; Murabayashi, Sho; Wei, Wei; Senoo, Keishi; Tokuchi, Naoko; Tateno, Ryunosuke (Frontiers in Environmental Science, 2015)
Topography affects the soil physicochemistry, soil N dynamics, and plant distribution and growth in forests. In Japan, many forests are found in mountainous areas and these traits are often highly variable along steep slopes. In this study, we investigated how the microbial population dynamics reflected the bioavailable N dynamics with the physicochemical gradient along the slope in soils of a natural forest in Japan. We measured the gross rates of NH4+ production, nitrification, and NH4+/ NO3− immobilization using the N isotope dilution method to analyze the N dynamics in the soils. We also determined the abundance of the bacterial 16S rRNA gene and bacterial and archaeal ammonia monooxygenase gene (amoA) using qPCR to assess the populations of total bacteria and nitrifiers. We found that gross rates of NH4+ production and nitrification were higher in the lower part of the slope, they were positively correlated with the abundance of the bacterial 16S rRNA gene and archaeal amoA, respectively; and the availability of N, particularly NO3−, for plants was higher in the lower part of the slope because of the higher microbial nitrification activity and low microbial NO3− immobilization activity. In addition, path analysis indicated that gross rates of NH4+ production and nitrification were regulated mainly by the substrate (dissolved organic N and NH4+) concentrations and population sizes of total bacteria and nitrifiers, respectively, and their population sizes were strongly affected by the soil physicochemistry such as pH and water content. Our results suggested that the soil physicochemical gradient along the slope caused the spatial gradient of gross rates of NH4+ production and nitrification by altering the communities of ammonifiers and nitrifiers in the forest slope, which also affected plant distribution and growth via the supply of bioavailable N to plants.